Legal framework of central-local government administrative relationship and its implication on the autonomy of local government authorities in Mainland Tanzania - Mnyasenga, Thobias Raphael (Mzumbe University, 2024)
A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy of Mzumbe University.